1987
DOI: 10.1002/kin.550190804
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of thermal eliminations part XXIII: [1] The thermal decomposition of pyruvic acid

Abstract: The thermal decomposition of pyruvic acid into carbon dioxide and acetaldehyde is a unimolecular first-order reaction and takes place according to the rate equation. loyk 13.53--41.250,'4.575 K. These parameters contrast markedly with those recently reported. viz. logk = 7.19-27.700/4.575 K and confirm that the latter, which gave an unacceptably low value for the frequency factor. are anomalous. The lower reactivity of p? rt1v:c acid compared to oxalic acid is interpreted in terms of normal electronic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 5 publications
2
41
0
Order By: Relevance
“…Earlier work on gas-phase elimination kinetics of pyruvic acid showed that the acid decomposes into carbon dioxide and acetaldehyde [1]. The mechanism proposed for this reaction involves a four-membered cyclic transition state with partial negative charge being developed at the ␣-carbonyl carbon, eq.…”
Section: Introductionmentioning
confidence: 98%
“…Earlier work on gas-phase elimination kinetics of pyruvic acid showed that the acid decomposes into carbon dioxide and acetaldehyde [1]. The mechanism proposed for this reaction involves a four-membered cyclic transition state with partial negative charge being developed at the ␣-carbonyl carbon, eq.…”
Section: Introductionmentioning
confidence: 98%
“…[5][6][7] In this paper, we report on the thermal gas-phase elimination of a-substituted propanoic acid and b-substituted 1-propanol, the substituent in both systems being an aryl moiety. Relative rate factors of 10 2 -10 7 have been observed, indicative of the major contribution to reactivity by the mesomerically electron-accommodating phenoxy group and its thio and amino analogues.…”
Section: Introductionmentioning
confidence: 99%
“…PA undergoes decarboxylation in the gas and aqueous phases by means of different mechanisms. Decarboxylation of gas phase PA has been seen to occur thermochemically, through IR multiphoton pyrolysis, as well as through UV and visible excitation (13,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36). The main removal pathway of gas phase PA from the troposphere is UV photolysis, with reaction with OH radical providing a minor contribution (31).…”
mentioning
confidence: 99%